Measurement of Pulmonary Artery Wave Reflection Before and After Mitral Valvuloplasty in Canine Patients With Pulmonary Hypertension Caused by Myxomatous Mitral Valve Disease - Yoshida, Tomohiko; Shimada, Kazumi; Hamabe, Lina; Uchide, Tsuyoshi; Tanaka, Ryou; Matsuura, Katsuhiro (Frontiers in Veterinary Science, 2021)
Background: Pulmonary arterial wave reflection provides novel information about pulmonary artery hemodynamics in pulmonary hypertension (PH). PH is common in dogs with myxomatous mitral valve disease (MMVD), though research examining the relationship between pulmonary arterial wave reflection and MMVD with PH is lacking. Hypothesis/Objective: This study investigated conventional echocardiographic parameters and pulmonary artery wave reflection parameters before and after mitral valvuloplasty in canine patients with PH due to MMVD. The parameters were backward pressure (Pb), forward pressure (Pf), and the reflection coefficient calculated as the ratio of peak Pb to peak Pf (RC). Animals: The study subjects were ten client-owned dogs receiving mitral valvuloplasty for MMVD with PH. Methods: Conventional echocardiographic parameters and pulmonary artery wave reflection parameters were measured before and after mitral valvuloplasty . The relationships between pulmonary artery wave reflection parameters and echocardiographic parameters, estimation of pulmonary artery systolic pressure, and right atrium pressure (RAP) gained by catheter in mitral valvuloplasty were also investigated. Postoperative echocardiography and the measurement of pulmonary arterial wave reflection were performed two weeks after mitral valvuloplasty . Results: The parameters of normalized left ventricular internal diameter at end-diastole (LVIDDN), E velocity, and the estimation of pulmonary artery systolic pressure were significantly reduced postoperatively compared with baseline measurements (p < 0.05). Postoperative Pb decreased significantly compared with preoperative measurements (8.8 ± 5.9 to 5.0 ± 3.2 mmHg, p = 0.037) as did RC (0.37 ± 0.15 to 0.22 ± 0.11, p < 0.01). A statistically significant positive correlation existed between wave reflection parameters and RAP, an estimation of pulmonary artery systolic pressure. Conclusions: Results demonstrate that mitral valvuloplasty can be used to treat secondary PH caused by MMVD, resulting in the improvement of postoperative echocardiographic and wave reflection parameters and a decrease in the right afterload. In some patients, some degree of vascular admittance mismatch persisted, despite the improvement of left atrial pressure. This may be indicative of residual pulmonary arterial disease, which may continue to adversely affect interactions between the right ventricle and the vasculature.